Le droit de vote des détenu-e-s - Bernheim, Jean; Millette, Renée (Criminologie, 1991)
The demand for the right of prisoners to vote has a history that shows how there has never been a right, a freedom, that was recognized without a social, political and legal fight. Rights and freedoms that are not won and whose exercice is not assured remain but words, perhaps merely dreams.